Marital status transitions and self-reported health among Canadians: A life course perspective - Zella, S (Springer, 2016)
This study focuses on the relationship between marital status transitions (the formation and dissolution of unions) and the self-reported health of adults in Canada. Empirical research has found that those in intimate unions generally enjoy better mental and physical health than the unattached and the dissolution of a union causes distress both for men and for women. Much remains to be understood about the effects of marital status transitions on health, especially from a life course perspective. This study poses the following research questions: do the number of marital status transitions and the kind of marital status transitions (from single to cohabitant; from single to married; from cohabitant to married and from married to divorce) affect health over time? Does difference between genders exist in this relationship? Data come from the nine cycles of the Canadian National Population Health Survey (1994–2011) and random-intercept logistic regression models are estimated to address these questions. Results do suggest that marital status transitions play a crucial role in determining health over time. Controlling for socio-demographic characteristics, marriage and cohabitation are associated with better physical and mental health, and depression symptoms are clearly stronger in cases of the dissolution of unions. Differences between genders are also evident.